Some Determinants of the Quality of Life in Patients Suffering from Multiple Sclerosis - Rashikj Canevska, Olivera; Chichevska Jovanova, Natasha (Faculty of Philosophy, Skopje, 2015)
People with multiple sclerosis are faced with numerous challenges which in turn may affect the things they want to do or have a need to do. Very often, constraints caused by the disease reduce their ability to cope with and meet their responsibilities at home, at work and within a broader community transforming simple daily activities into daily frustrations. The main goal of the research process was to present the life of persons with multiple sclerosis in the Republic of Macedonia, the problems they face every day, and the way they exceed them. We used the methods of structural, descriptive and functional analysis, as well as the method of generalization. We applied data (document) analysis, scaling and inquiry, and as a basic instrument we used a questionnaire composed of a combination of several scaling and index assessments. There was a convenient sample of the research composed of 32 persons with multiple sclerosis over the age of 18, and the results were obtained by a statistical analysis of the data and application of the combination of chi square tests, with a p<0.05 level of significance.According to the results of the Index of disability, 47% of the people with multiple sclerosis have limited independence in providing daily activities leading up to 31% of the examinees with rare participation in the everyday social activities, the result obtained by the Frenchay Index of activities. We can conclude that the Index of disability is higher with older respondents and it is often followed by a drop of the daily activity frequency.
Некои аспекти за квалитетот на животот кај лицата болни од мултиплекс склероза
Keywords: multiple sclerosis, quality of life, index of disability, independence.